AGROTECHNOLOGICAL AND ECONOMIC IMPORTANCE OF THE HEAT SUPPLY FORECASTING FOR THE POST-HARVEST PERIOD IN THE DRY STEPPE ZONE OF UKRAINE - Oleksandr RUDIK; Raisa VOZHEHOVA; Pavlo LYKHOVYD; Leonid SERHIEIEV; Viktor CHUHAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the study is to assess available agroclimatic resources and forecast heat supply in the post-harvest period in the Dry Steppe zone of Ukraine. Dynamic analysis of agrometeorological indices was performed by comparing the average long-term values. The correlation analysis of the agroclimatic conditions of the growing season revealed a significantly strong dependence of individual meteorological indices on the availability of heat resources in the post-harvest period. It was established that the sum of effective and active temperatures for the post-harvest period has a weak and moderate correlation with the mean monthly air temperature and atmospheric aridity index in April and May, while in June the coefficient increases. The highest correlation of the specified meteorological parameters was recorded for the period 1992–2021. Linear regression models of the dependence of the sum of active and effective temperatures during the post-harvest period with high adequacy (R2=0.69–0.70) were developed. The models allow forecasting the temperature conditions for placing the fore crops for winter wheat. Besides, they are useful for better selection of varieties and hybrids for the post-harvest crops of sunflower and millet. As a result, 28.31% higher yields of millet, and 15.77% higher yields of sunflower in 2022-2023, comparing to 2021, were collected owing to better choice of suitable crops’ genotypes. The economic effect of the methodology reached additional 220 EUR/ha for millet, and 80 EUR/ha for sunflower, respectively. The implementation of this method contributes to a more productive use of natural resources and an increase in crop productivity and profitability.